STUDI PEMETAAN SPEKTRUM KEAHLIAN LULUSAN PROGRAM STUDI PENDIDIKAN TEKNIK ELEKTRO UNIVERSITAS NEGERI PADANG - Siregar, Winda Lestari; Yudhi Diputra; Jalius, Nizwardi Jalinus; Ridwan; Rijal Abdullah; Nurhasan Syah (The Indonesian Journal of Computer Science, 2024)
Upon graduation, the aim of education graduates is to become qualified educators capable of meeting the needs of education, society, and industry. Graduates of the Electrical Engineering Education Study Programme are expected to possess superior competence and provide solutions to societal problems. The research conducted is descriptive in nature, utilising a qualitative approach. The study was carried out at the Faculty of Engineering, State University of Padang. The research instrument comprised documents such as course outlines, course synopses, and syllabi in Electrical Engineering Education at Padang State University. Data was collected through interviews and documentation. The study aimed to create a mapping of Electrical Engineering Education courses at Padang State University. The UNP Electrical Engineering Education program requires students to complete a set number of courses each semester. In semester 1, students must complete 22 SKS; in semester 2, 22 SKS; in semester 3, 22 SKS; in semester 4, 19 SKS; in semester 5, 22 SKS; in semester 6, 20 SKS; in semester 7, 8 SKS; and in semester 8, 10 SKS of final courses. The requirement for Semester Credit Units for Electrical Engineering Education students at Padang State University is 145 credits.